Physical parameters influence the microbial quality of indoor air in research laboratories: a report from Malaysia - Yogeswaran, Kuilan; Azmi, Liyana; Bhassu, Subha; Isa, Hafizah Noor; Aziz, Muhamad Afiq (Elsevier, 2023)
The quality of air conditioning and ventilation systems in laboratories is vital to ensure optimum health of the users and guarantee the accuracy of experiments conducted. Moreover, recent studies show that the average quality of air conditioning and ventilation systems in labs can pose health risks to occupants. The study aims to examine the relationship between physical parameters and microbial pollutants in research laboratories' indoor air quality (IAQ) by quantifying and characterising the bacteria and fungi in the indoor environment of research laboratories using the settle plate method; whereby our Petri dishes containing media are exposed to the air for sample collection. This study was conducted over the course of 3 day at three different research laboratories: Virology Lab (VL), Genetic Lab (GL), and Aquatic Lab (AL). The physical parameters such as air temperature, humidity and carbon dioxide were measured using FLUKE 975 air meter, whereas the microbial parameters were assessed using the settle plate method with Tryptone Soya agar and Sabouraud Dextrose agar for the bacterial and fungal count, respectively. Our results showed that the high temperature and relative humidity, exceeded the standard threshold for temperature (23–26 C) and relative humidity (40–70%) set by the Department of Occupational Safety and Health (DOSH). Additionally, because of poor air conditioning and ventilation system maintenance, there were high total bacterial counts in GL (CFU/m3 234.34 30.93) and total fungal counts in VL (CFU/m3 589.34 53.03). We also showed that the most commonly isolated bacteria and fungi in research laboratories were Staphylococcus spp. (72.2%) and Cladosporium spp. (76.7%). In conclusion, we reported that there was a correlation between the physical parameters and microbial pollutants in the research laboratories. Therefore, regular monitoring of indoor air quality (IAQ) parameters and maintenance of the air conditioning and ventilation system should be carried out to ensure a good and safe indoor environment in research laboratories